Pemanfaatan Rapot Mutu Pendidikan (RMP) sebagai Informasi Strategis dalam Perencanaan di UPTD SDN 2 Bati-Bati: Utilization of Education Quality Report (RMP) as Strategic Information in Planning at UPTD SDN 2 Bati-Bati - Sri Meldayani; Wiwik Indrasari; Sulistiyana Sulistiyana; Suhaimi Suhaimi (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
This study aims to analyze the use of the Education Quality Report (RMP) as a strategic information resource in school planning at UPTD SDN 2 Bati-Bati. Data-driven planning is a crucial approach in modern education management because it enables more objective, targeted, and measurable decision-making. This research employed a qualitative case study design. Data were collected through in-depth interviews, observation, and documentation, and analyzed using an interactive analysis model encompassing data reduction, data presentation, and conclusion drawing.The results indicate that the RMP is systematically utilized in the school planning process, from quality indicator analysis and problem and root cause identification to priority program formulation. RMP data is integrated into the school's main planning documents, namely the Education Unit Curriculum (KSP), School Work Plan (RKS), and School Work and Budget Plan (RKAS). This utilization results in programs that are more relevant to the school's actual needs, clear, measurable targets, and more effective, targeted budget management.Furthermore, the RMP serves as a tool for schools to improve educational quality continuously. However, this study found that increasing human resource capacity, particularly in data analysis, is still necessary to optimize the use of RMP. Therefore, RMP plays a strategic role in supporting data-driven planning and improving the quality of education in educational institutions.